Avaliação ambiental por geoprocessamento, como base ao plano diretor municipal de Faxinal do Soturno - RS - Kersten, Diogo Silveira (2009)
The growing demand for life quality due, mainly, by consumerism, has created a greater exploitation of natural resources, increasing deforestation, urban occupations in inappropriate areas, the expansion of consumption of surface water but also groundwater, to meet the many different uses, with a consequent increase in indiscriminate pollution. This work, realized in Faxinal do Soturno city, situated in the central region of Rio Grande do Sul state, has as objectives identify the suitable areas for the use and occupancy, vulnerable areas to contamination and identify some potential contaminants human activities that can affect the groundwater quality, as they are used in large-scale by Faxinal do Soturno population. In this study we used primary data, obtained in the field, and pre-existing data, obtained from SIAGAS (Sistema de Informação de Águas Subterrâneas) and spatializated in ArcGIS 9.2 and Surfer 8.0 applications, which generated the basic thematic mapping. The research was based on the type of geoprocessing environmental assessment based on SAGA (Sistema de Análise Geo-Ambiental) application, which could be performed the planimetry interaction with the maps of slope, geology, soil and static level, to get the map of natural vulnerability of aquifers contamination, which was faced with a map of potentially contaminating activities. The analysis showed one area of 3,950.95 hectares as of low vulnerability, this able to use and occupation, and 25.85 hectares as of extreme vulnerability, which suggests immediate mitigating measures. In SAGA evaluations, we found that the Faxinal of Soturno is located in an average vulnerability area, where there are potentially contaminating activities such as the cemetery, the hospital and fuel stations, which were georeferenced. The suitable and unsuitable areas for the use and occupation were found by the evaluation of the complex map of natural vulnerability, collate before the map of environmental risk, which was found an area of 1,440.85 ha without restriction on the use and occupation, and area of 2,666.82 ha for unsuitable areas for use. So, with those results obtained by the environmental analysis, one can say that the area without restriction must be a priority for the occupation, and demand the fulfillment of measures limiting the free use to the allocation of potentially contaminating activities, which will be installed in the municipality of Faxinal do Soturno.